Sikap dan Masalah Guru Pelatih dalam Menjalani Latihan Mengajar - Kasa, Zakaria; Md Aroff, Abdul Rahman (Universiti Putra Malaysia Press, 1995)
Practical teaching is an important component in the teacher education programme, as it exposes students to the actual teaching environment. A study was conducted to identity the attitude of student teachers towards practical teaching and the problems they faced during practicum. The population comprised UPM student teachers of the December semester 1993/94. The systematic cluster sampling technique was used to select the sample of 215 student teachers. The findings showed that, in general, student teachers have a positive attitude towards practical teaching; this attitude was found to have a significant relationship with teaching experience. Student teachers without teaching experience were found to have a more positive attitude towards practical teaching than those who had teaching experience. The findings also showed that student teachers found difficulties in (I) teaching with full concentration in the time frame given,(2) choosing appropriate audiovisual teaching aids, (3) choosing appropriate teaching methods, (4) knowing the background of every student that he/she taught, (5) remembering the names of all students he/she taught, (6) solving financial problems, (7) solving the problem of anxiety, and (8) preparing various types of questions. Two of these problems, i.e. the difficulties of choosing appropriate audiovidual teaching aids and teaching methods, had significant relationships with attitude towards practical teaching.